2013
DOI: 10.1016/j.jadohealth.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Provision of Long-Acting Reversible Contraception Among Adolescent Health Care Providers

Abstract: Purpose To identify provider and practice characteristics associated with long-acting reversible contraception (LARC – progesterone contraceptive implants or IUDs [intrauterine devices]) provision among adolescent health care providers. Methods We analyzed physician characteristics and self-reported provision of LARC using chi-square analyses. Multivariate logistic regressions identified factors predicting provision of any form of LARC, as well as progesterone contraceptive implants or IUDs specifically. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 9 publications
2
42
1
Order By: Relevance
“…This recommendation is consistent with findings from previous research on LARC 22-25 . Future studies should assess the impact over time on providers' counseling skills and confidence in LARC methods with the introduction of provider training and increased access to LARC methods.…”
Section: Discussionsupporting
confidence: 92%
“…This recommendation is consistent with findings from previous research on LARC 22-25 . Future studies should assess the impact over time on providers' counseling skills and confidence in LARC methods with the introduction of provider training and increased access to LARC methods.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of knowledge among adolescents can largely be attributed to a lack of counseling by providers due to biases regarding the LARC methods, as well as a lack of understanding regarding the safety and effi cacy of their use in adolescents. 20,21 Perceived pain with the insertion of the LARC methods, in particular IUDs, is another barrier to their uptake among adolescents. 18,19 Contraceptive implants require little instruction beyond the FDA-mandated training and no additional equipment is needed beyond the implant inserter; however, implants are used even less frequently than IUDs due to providers' lack of knowledge regarding implants as a contraceptive option.…”
Section: ■ Barriers To Larc Use In Adolescentsmentioning
confidence: 99%
“…In cases where pregnancy is unlikely but cannot be absolutely ruled out, the CDC does suggest that inserting the implant could be considered as long as the patient is instructed to return for a pregnancy test in 2 to 4 weeks. 20 Patients should be counseled regarding the quick return to fertility following removal of the ENG implant and offered another method of contraception if they are not planning to become pregnant. Prior to insertion, it is recommended that providers counsel patients on the bleeding irregularities that can occur with the implant.…”
Section: ■ Best Practices For Insertion and Adherence Of Eng Implantsmentioning
confidence: 99%
“…6 Despite an upsurge of interest in LARC, there is no standardized LARC training in pediatric residency programs or adolescent medicine fellowships. This lack of training poses one of many barriers to young women trying to access these methods.…”
mentioning
confidence: 99%
“…One study found that only one-quarter of adolescent medicine clinicians were trained to insert intrauterine devices (IUDs) or implants. 6 Given the lack of adequate knowledge about LARC among general pediatricians, this number is likely much lower for clinicians without specific adolescent training. 7 Lack of onsite insertion presents a significant barrier to LARC use in young women.…”
mentioning
confidence: 99%